Does the Degree of Cystocele Predict De Novo Stress Urinary Incontinence After Prolapse Repair? Further Analysis of the Colpopexy and Urinary Reduction Efforts Trial. Issue 4 (July 2018) - Davenport, Michael T.; Sokol, Eric R.; Comiter, Craig V.; Elliott, Christopher S.
Abstract : Introduction: Cystoceles may cause urethral obstruction by altering the vesicourethral angle. Restoration of normal anatomy after pelvic organ prolapse (POP) repair can relieve this obstruction but may unmask stress urinary incontinence (SUI). The association between the severity of cystocele and developing de novo SUI after prolapse repair, however, is poorly understood. We hypothesized that, in women undergoing prolapse repair, increasing degrees of bladder prolapse would be associated with increasing rates of postoperative de novo SUI. Materials and Methods: We performed a secondary analysis of the Colpopexy and Urinary Reduction Efforts (CARE) trial data. Using the control arm (women undergoing prolapse repair without a prophylactic SUI procedure), we identified de novo SUI using a composite definition based on original trial criteria. We performed logistic regression to evaluate the relationship between the degree of cystocele and the development of new SUI. Results: Of the 164 women who underwent abdominal sacrocolpopexy alone, 54% developed de novo postoperative SUI. Stratifying by the degree of anterior prolapse (point Ba), we found a linear increase in the rate of SUI with worsening preoperative cystocele. The incidence of de novo SUI based on the POP Quantification stage of anterior prolapse was 41.3%, 52.5%, and 66.1%, for stage 2, early stage 3, and advanced stage 3 or stage 4, respectively. Point Ba was found to be significantly associated with de novo SUI on both univariate (odds ratio = 1.17, P = 0.015) and multivariate analysis (odds ratio = 1.16, P = 0.04). Conclusions: The incidence of de novo SUI after prolapse repair directly correlates to the degree of cystocele on preoperative examination. This simple yet novel relationship should further guide discussions about potential postoperative incontinence. Abstract : Increasing degree of anterior prolapse is associated with increased odds of postoperative de novo stress urinary incontinence after apical prolapse repair.